2020
DOI: 10.34172/jhp.2020.47
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antiplasmodial assays of selected Nigerian commercial herbal formulations

Abstract: Introduction: Malaria remains a life-threatening disease, mainly in tropical and sub-tropical countries of the world. The problem caused by the disease is further compounded by the emergence and spread of multidrug resistant Plasmodium falciparum. Coupled with the poor distribution of modern health facilities, there is resurgence in the use of herbal remedies to treat malaria. In this study, we evaluated the antiplasmodial activities of six commercially available herbal formulations using in vivo and in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Infected cells including erythrocytes are always under oxidative stress; therefore in some disease conditions it is helpful for 19 The result showed that African iba herbal formulation has a very promising in vitro antiplasmodial activity with IC50 value of 9.61 µg/mL against chloroquine resistant plasmodium falciparum (DD2). This result is in contrast to the earlier result obtained by Ikem et al, (2020) which stated that IC50 of African iba against chloroquine sensitive plasmodium falciparum (3D7) had a poor activity over 100 µg/mL. 14 This could be attributed to the difference in genetic makeup between both parasites.…”
Section: Cytotoxicity (Jukart Cell Line and Red Blood Cells)mentioning
confidence: 57%
See 4 more Smart Citations
“…Infected cells including erythrocytes are always under oxidative stress; therefore in some disease conditions it is helpful for 19 The result showed that African iba herbal formulation has a very promising in vitro antiplasmodial activity with IC50 value of 9.61 µg/mL against chloroquine resistant plasmodium falciparum (DD2). This result is in contrast to the earlier result obtained by Ikem et al, (2020) which stated that IC50 of African iba against chloroquine sensitive plasmodium falciparum (3D7) had a poor activity over 100 µg/mL. 14 This could be attributed to the difference in genetic makeup between both parasites.…”
Section: Cytotoxicity (Jukart Cell Line and Red Blood Cells)mentioning
confidence: 57%
“…This result is in contrast to the earlier result obtained by Ikem et al, (2020) which stated that IC50 of African iba against chloroquine sensitive plasmodium falciparum (3D7) had a poor activity over 100 µg/mL. 14 This could be attributed to the difference in genetic makeup between both parasites. 27 From the manufacturers claim it was observed that African Iba herbal formulation was prepared using Kigelia africana and Nauclea latifolia.…”
Section: Cytotoxicity (Jukart Cell Line and Red Blood Cells)mentioning
confidence: 57%
See 3 more Smart Citations